Impact of narrow-band ultraviolet B radiation therapy on the quality of life of patients with vitiligo. Issue 6 (December 2021) - Khojah, Hani M.J.; Alharbi, Assaf G.; Alshaeri, Abdulrahman A.; Alahmadi, Yaser M.; Elbadawy, Hossein M.
الملخص: أهداف البحث: يعاني مرضى البهاق من الضغط النفسي والعاطفي أثناء خضوعهم لعلاج طويل الأمد. والآثار النفسية والاجتماعية الموهنة لهذا المرض، التي تؤثر على جودة حياة المرضى موثقة جيدا. في هذه الدراسة، قمنا بتقييم تأثير إضافة العلاج بالأشعة فوق البنفسجية ضيقة النطاق على جودة حياة مرضى البهاق في منطقة المدينة المنورة، المملكة العربية السعودية. طرق البحث: تمت مقابلة ٣٨ مريضا من مركز الأمراض الجلدية الرئيس في المدينة المنورة (مستشفى أحد) باستخدام نموذج مؤشر جودة الحياة للأمراض الجلدية قبل وبعد عام واحد من دورة العلاج باستخدام الأشعة فوق البنفسجية ضيقة النطاق، التي أضيفت إلى نظامهم العلاجي الأساسي مع استمرار استخدامهم للمستحضرات الدوائية الموضعية. النتائج: كانت استجابة المرضى لعلاج البهاق إيجابية. النتيجة الإجمالية لرضا المرضى فيما يتعلق بالعلاج بالأشعة فوق البنفسجية ضيقة النطاق كانت مرتفعة لتصل إلى ٩.١ من ١٠. وقد انخفضت النتيجة الأولية العامة لمؤشر جودة الحياة للأمراض الجلدية (٥.٦٧± ٠.٩٠) بشكل ملحوظ بعد العلاج المتضمن استخدام الأشعة فوق البنفسجية ضيقة النطاق (٣.٠٨ ± ٠.٥٦)، مما يشير إلى وجود تحسن. كما تحسن التزام المرضى بزيارات المتابعة والجلسات العلاجية. الاستنتاجات: علاج البهاق المتضمن استخدام الأشعة فوق البنفسجية ضيقة النطاق فعال في تخفيف الضغط النفسي وتحسين جودة الحياة لدى مرضى البهاق. Abstract: Objectives: Patients with vitiligo experience emotional and psychological stress as they undergo long-term therapy. The debilitating psychosocial effects of this disease on patients' quality of life is well-documented. This study evaluates the effect of the introduction of narrow-band ultraviolet-B (NB-UVB) therapy on the quality of life of patients with vitiligo in Almadinah Almunawwarah, KSA. Methods: Thirty-eight patients from the main dermatology center of Ohud Hospital, Almadinah Almunawwarah, were interviewed between June 2017 and March 2019 using the Dermatology Life Quality Index (DLQI) questionnaire. The interviews were conducted before and one year after the course of NB-UVB therapy, which was added as a new treatment modality to the basic therapeutic regimen of topical medications. Results: The patients' response to vitiligo therapy was positive. The overall patient satisfaction score regarding the NB-UVB therapy was as high as 9.1 out of 10. The initial overall DLQI score (5.67 ± 0.90) markedly decreased after the NB-UVB therapy (3.08 ± 0.56), indicating a significant improvement. The patients' adherence to the follow-up visits also improved. Conclusion: NB-UVB therapy is effective in alleviating psychological stress and improving the quality of life of patients with vitiligo.